Influence of Partner Support on an Employed Mother's Intention to Breastfeed After Returning to Work - Tsai, Su-Ying (Mary Ann Liebert, Inc., 2014)
Background: Despite the increasing number of large companies complying with the demands for a breastfeeding-friendly workplace, providing on-site lactation support, some mothers still find continuing to breastfeed a challenge. We postulated that greater support and encouragement from the partner would be independently predictive of whether the mother would take advantage of workplace milk expression breaks and lactation rooms and continue to breastfeed after returning to work. To evaluate this hypothesis, we conducted a survey at a female labor-intensive electronics manufacturer in Taiwan. Subjects and Methods: Six hundred eight working mothers in an electronics manufacturing plant in Tainan Science Park in Southern Taiwan who had access to dedicated lactation rooms at the workplace were interviewed. Questionnaire content included female employee demographics, employment characteristics, partner-related characteristics, and breastfeeding behavior after returning to work following the birth of their most recently born child. Results: The partner's initial support of the choice to breastfeed and encouragement to use the lactation room and milk expression breaks and the mother's perception of the partner's support for baby care were significant predictors of the intention to continue to breastfeed after returning to work, after adjusting for the employed mother's demographics and employment characteristics, supporting our hypothesis. Conclusions: These findings suggest that antenatal education or activities provided by the workplace should include the partner, which may improve workplace breastfeeding rates.